2003
DOI: 10.1086/378588
|View full text |Cite
|
Sign up to set email alerts
|

Common and Unique Susceptibility Loci in Graves and Hashimoto Diseases: Results of Whole-Genome Screening in a Data Set of 102 Multiplex Families

Abstract: The autoimmune thyroid diseases (AITDs), comprising Graves disease (GD) and Hashimoto thyroiditis (HT), develop as a result of a complex interaction between predisposing genes and environmental triggers. Previously, we identified six loci that showed evidence for linkage with AITD in a data set of 56 multiplex families. The goals of the present study were to replicate/reject the previously identified loci before fine mapping and sequencing the candidate genes in these regions. We performed a whole-genome linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
188
1
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 209 publications
(198 citation statements)
references
References 60 publications
4
188
1
5
Order By: Relevance
“…Both disorders are common with a prevalence in the United States of approximately 1%. 22,23 While the etiology is unknown, AITDs are considered complex diseases, caused by an interaction between susceptibility genes 24,25 and non-genetic factors. Among the environmental factors implicated in the etiology of AITD are hepatitis C infection 26 and IFN␣ therapy.…”
Section: Autoimmune Interferon Induced Thyroiditismentioning
confidence: 99%
See 1 more Smart Citation
“…Both disorders are common with a prevalence in the United States of approximately 1%. 22,23 While the etiology is unknown, AITDs are considered complex diseases, caused by an interaction between susceptibility genes 24,25 and non-genetic factors. Among the environmental factors implicated in the etiology of AITD are hepatitis C infection 26 and IFN␣ therapy.…”
Section: Autoimmune Interferon Induced Thyroiditismentioning
confidence: 99%
“…The hallmarks of GD are the presence of clinical hyperthyroidism with positive TSHR antibodies and/or diffusely increased radioactive iodine intake on thyroid scan. 40 Because HT and GD are believed to have shared immunogenetic etiology 24 it is not surprising that treatment with IFN␣ can also result in the development of GD. 13,30 A retrospective review of 321 patients with hepatitis B or C treated with IFN␣ by Wong et al, found 10 patients who developed thyrotoxicosis characterized by a completely suppressed TSH.…”
Section: Autoimmune Interferon Induced Thyroiditismentioning
confidence: 99%
“…Association studies using three common TSHR exonic and nonsynonymous SNPs (in the extracellular and intracellular domain of the receptor) were inconsistent (5,6,(8)(9)(10)(11)(12). However, in two linkage studies we described a GD-specific chromosome 14 locus of *25 cM, designated GD-1 (4,7,13), in the center of which was the TSHR (between markers D14S258 and D14S1054). GD-1 was consistently linked with GD and not with Hashimoto's thyroiditis (HT) (7).…”
Section: Introductionmentioning
confidence: 95%
“…However, in two linkage studies we described a GD-specific chromosome 14 locus of *25 cM, designated GD-1 (4,7,13), in the center of which was the TSHR (between markers D14S258 and D14S1054). GD-1 was consistently linked with GD and not with Hashimoto's thyroiditis (HT) (7).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In addition, association analysis using microsatellite markers confirmed evidence for the presence of susceptibility genes in or near 5q23-q33 in a Japanese cohort. 5 This could suggest that these factors are only contributing to GD in the Asian population and not to disease susceptibility in Caucasian populations.…”
Section: Discussionmentioning
confidence: 66%